La dieta del jaguar (Panthera onca), el puma (Felis concolor) y el manigordo (Felis pardalis) (Carnivora: Felidae) en el Parque Nacional Corcovado, Costa Rica - Chinchilla, Federico A (1997)
The diets of the jaguar (Panthera onca), the puma (Felis concolor) and the ocelot (Felis pardalis) were studiedin a tropical rainforest in Corcovado National Parle, South Pacific belt of Costa Rica, from August 1993 to June 1994. A total of 50 Km of trails were examined month1y for fecal material. Analysis of relative frequency of ocUrrence and telative estimation bionlass in the fecal samples showed that mammals were the main preys of the three feüds, while reptiles and birds were less important. The preys of jaguar and puma have body weights aboye 2500g, and the preys of ocelot, whose main prey was the spiny rat, Proechimys semispinosus, less than 2500g. Thete wéteno important changes in foad habits during the stu'dy, although trophic diversity of jaguar and ocelot increase during the dry seasons.